Assessment of circulating fibroblast growth factor 23 in type 2 diabetic patients with nephropathy - OLA SAYED M. ALI,; MOHAMED H. MAHFOUZ,; RIHAM A. ZIDAN, (International Journal of Pharma and Bio Sciences, 2017)
About one third of type 2 diabetics will eventually have progressive deterioration of renal function. Fibroblast growth factor 23(FGF23) is one of the main bone-derived endocrine hormones that plays many regulatory functions in different body systems especially in kidneys. In the current study, significantly increased FGF23 levels were observed in micro- and macroalbuminuric diabetic groups when compared to the control and normoalbuminuric diabetic groups. FGF23 found to correlate positively with duration of diabetes, serum creatinine and ACR, but correlate inversely with GFR in DN groups.Receiver operating characteristic curves revealed that for early detection of DN , the best cutoff values to discriminate DN and diabetic without nephropathy groups were 430.1 pg/mL for FGF23 with 80.8% sensitivity, 53% specificity, and area under the curve (AUC) = 0.773; 25 mg/g creatinine for ACR with 100% sensitivity, 95% specificity, and AUC = 1. ACR was more sensitive and specific than FGF23.therefore, we can conclude that FGF23 is associatedwith the different stages of DN but is less sensitive and specific than ACR for early detection of nephropathy in diabetic patients. In fact, additional studies are needed to assess the signiï¬cance of changes in FGF23 levels during the course of DN.